State of Art: Behavior of High-Strength Concrete with and Without Steel Fiber Reinforcement - Mahdi, Liqaa Salam; Mohammed, Prof. Dr. Hussam Ali (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Steel fibered high-strength concrete (SFHSC) has emerged as a widely utilized material in structural engineering due to its superior durability and aesthetic benefits. Its strength enhances structural performance, making it particularly valuable in dynamic loading conditions. Extensive research has been conducted to optimize fiber content, identify suitable fiber types, and integrate SFHSC with conventional reinforcement to improve ductility and mitigate macro-crack propagation. Additionally, composite two-layer beams combining SFHSC with normal-strength concrete offer cost-effective solutions for new constructions and retrofitting applications. Recent experimental studies have provided valuable insights into SFHSC properties, existing design codes, and potential advancements in modern structural engineering. [ 1 ].